Advancing scholarly writing of baccalaureate nursing students using the knowledge, skills, and attitude self-assessment for writing development. (October 2018) - Shellenbarger, Teresa; Gazza, Elizabeth A.; Hunker, Diane F.
Abstract: Background: Baccalaureate nursing students often demonstrate basic oral and written communication skills and have varying levels of skill with scholarly writing. Current instructional approaches may not fully prepare students for scholarly writing expectations. Objective: To determine undergraduate baccalaureate nursing students' self-assessed ability to demonstrate the knowledge, skills, and attitudes of scholarly writing. Design: Quantitative correlational descriptive study. Setting: Undergraduate nursing programs in the United States. Participants: A convenience sample of baccalaureate nursing students in the United States. Methods: A national sample of 125 undergraduate nursing students self-assessed their use of the knowledge, skills, and attitudes of scholarly writing over a two-month period. The project also sought to determine the association between writing knowledge, skills and attitudes and demographic variables of baccalaureate nursing students. Results: Participants believe they know the basic components of scholarly writing. However, they have difficulty using abstract components of writing such as managing the emotional aspect associated with writing. Select personal and demographic variables were not associated with scholarly writing self-assessment, indicating that other factors may influence scholarly writing development. Conclusion: Teaching and learning strategies that incorporate the knowledge, skills, and attitudes associated with scholarly writing can be used to advance current instructional approaches and ultimately, better facilitate writing development in baccalaureate nursing students. Self-assessments can be used to identify ongoing student development needs for scholarly writing and can direct writing instruction.